Konsep Wakaf dalam Ilmu Manajemen - Aulya Rachma Damayanti; Silvia Aluf; Nazwa Abidin Yunus; Muhammad Faiz Ferdi Rahman; Danendra Sakhi Rukmana; Yayat suhayat (Pusat Riset dan Inovasi Nasional, 2023)
Waqf is one of the Muamalah activities that has spiritual, social and economic dimensions. Traditionally, waqf has so far only been interpreted as grants in the form of real estate such as land and buildings, whose purpose is limited to the construction of places of worship and educational institutions. Waqf is divided into several types based on purpose, time limit, and goods and their management. Management is the process of planning, organizing, directing and controlling an organization. Management occupies the most important place in the Waqf world because it can determine whether waqf assets are useful and developed depending on the management model. The purpose of the research is to study waqf in management science, the principles of waqf management and the function of waqf management. This research uses qualitative methods where researchers must analyze theoretical sources from books and journals as well as materials and information from various other secondary data to answer the problems studied. The findings, and implications that arise are found in the professionalism of waqf management, asset management in waqf, financial statements, contributions and potential economic development of the community with waqf in the digital era.